Inovação organizacional: um estudo de caso em pequenos negócios que atuam em mercados emergentes no RS - Soares, Marcela (Universidade do Vale do Rio dos Sinos, 2018)
This paper aims at proposing a set of guidelines for the elaboration of strategies of organizational innovation so that the small businesses attend the market of the base of the socioeconomic pyramid (BoP) of Rio Grande do Sul. The same was based on academic gaps related to The need for advances in research on organizational innovation run by small businesses, the need to understand the dynamics of innovation in companies that provide products to the base of the global economic pyramid, considering that this is the most vulnerable economic layer of society and investigate how innovation can increase the capacity for innovation and product development in small businesses. It has also considered the social and economic importance of small businesses for regional and country development, since they account for a significant part of their economy. The theoretical framework presents data related to innovation; potential emerging market: the base of the pyramid; and organizational innovation and small business. As a research method, a multiple case study with exploratory and descriptive character and a qualitative approach was adopted, applied in 25 small agribusiness businesses, food sector and located in the State of Rio Grande do Sul. The main results indicate that there is a fragility in relation to the development of specific products to serve less favored social classes by small businesses and reinforce market potential in financial and cultural constraints, but there is a lack of guidance in the definition of effective strategies. In addition, it becomes evident that small businesses can corroborate with the economic and social development of the base of the pyramid through the supply of products that meet their needs and also generate employment and income for the population located in the BoP. For this, a set of guidelines were organized based on the constructs taken from the theoretical framework: organizational configuration; product development; marketing and sales strategies; and supply chain, supply and sustainability. These guidelines aim to direct the development of effective organizational innovation strategies for small businesses to act in BoP, making decision making easier and making them more competitive and profitable in this market niche.
Keywords: Inovação organizacional; Mercados emergentes; Base da pirâmide; Pequenos negócios; Organizational innovation; Emerging markets; Base of the pyramid; Small business; ACCNPQ::Engenharias::Engenharia de Produção